Factors affecting the utilization of solar energy: An approach to sustainable rural development in Iran - Hatamifard, Sevil; Farajallah Hosseini, Seyed Jamal; Mirdamadi, Seyed mehdi (Frontiers in Energy Research, 2023)
This study was conducted to investigate the role of factors affecting the utilization of solar energy for the sustainable rural development of Zanjan Province. The statistical population in this study was rural households who used solar energy technology in Zanjan Province, and 210 households were selected as a sample using Kerjesi & Morgan’s table. The data collection tool was a questionnaire. The face and content validity of the questionnaire was confirmed by a panel of experts before the pre-test. The reliability of the research tool was also confirmed by conducting a pre-test among thirty people other than the statistical sample and calculating Cronbach’s alpha for the main scales of the questionnaire (in the range of 0.72–0.90). Data were analyzed using SPSS24 and AMOS22. The data were analyzed using structural equation modeling. The results showed a positive and significant relationship between educational, socio-cultural, policymaking, and environmental factors and the utilization of solar energy, and these variables explained 37% of the variance of the dependent variable. However, a weak significant relationship was observed between economic and technical factors with the utilization of solar energy. The finding of this study has some meaningful policy implications. The energy costs, sunlight coverage, and the efficiency of solar energy systems have caused solar energy to be considered as a suitable alternative for providing electricity and heating in rural areas of Iran.